PENGAWETAN LIMA JENIS KAYU MENURUT METODE RENDAMAN PANAS-DINGIN - Barly Barly; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The degree of protection offerd by a wood preservative depends upon the quality of preservative retained by the timber, the depth penetration, and the permanence of preservative in the wood.On the hot and cold bath process, the timber is immersed in cold preservative and the bath and timber are heated up together to around 70°C for one, two, three hours until the timber is hot throught, and the whole then allowed to cool down for 24 hours.For all timber species tested in this experiment the depth of penetration and retention of preservative was measured after treatment. The result of which can be seen in Table 1. After calculated and analysis (Table 2 and Table 3) the following conclusions could be draw :Timber species has highly significant on boron penetration and retention. Boron penetration a seemed to be generally getting deeper with increased hot soaking hours; but one hour is fully.Generally speaking, hot and cold bath process are to be preferred although with mahoni (Swietenia mahogani Jack:) and tanjung (Mimmusops elengi L.) timbers the preservative retention less than the other timbers.